AR Construction Technology of Blended English Teaching Mode in Colleges. (18th August 2022) - Wu, Xiaoliang; Gao, Pengfei
Abstract : Because the educational goals set by the traditional teaching mode are too single, students gradually lose interest in learning. In the information age, there are more and more cases of various emerging technologies being applied to the field of education, and college English education should also be strengthened. The application of these technologies will help to realize the diversified development of the presentation of teaching content. AR has developed rapidly. It can help people connect with the virtual world, obtain information in real time, and apply it in teaching classrooms to help students participate in knowledge exploration and strengthen student-student and teacher-student interaction. This research designs and develops a blended English case teaching resource based on AR, applies the teaching resource to the classroom of universities, and then tests the application effect of the resource.